European emissions of the powerful greenhouse gases hydrofluorocarbons inferred from atmospheric measurements and their comparison with annual national reports to UNFCCC. (June 2017) - Graziosi, F.; Arduini, J.; Furlani, F.; Giostra, U.; Cristofanelli, P.; Fang, X.; Hermanssen, O.; Lunder, C.; Maenhout, G.; O'Doherty, S.; Reimann, S.; Schmidbauer, N.; et al.
Abstract: Hydrofluorocarbons are powerful greenhouse gases developed by industry after the phase-out of the ozone depleting chlorofluorocarbons and hydrochlorofluorocarbons required by the Montreal Protocol. The climate benefit of reducing the emissions of hydrofluorocarbons has been widely recognised, leading to an amendment of the Montreal Protocol (Kigali Amendment) calling for developed countries to start to phase-down hydrofluorocarbons by 2019 and in developing countries to follow with a freeze between 2024 and 2028. In this way, nearly half a degree Celsius of warming would be avoided by the end of the century. Hydrofluorocarbons are also included in the basket of gases controlled under the Kyoto Protocol of the United Nations Framework Convention on Climate Change. Annex I parties to the Convention submit annual national greenhouse gas inventories based on a bottom-up approach, which relies on declared anthropogenic activities. Top-down methodologies, based on atmospheric measurements and modelling, can be used in support to the inventory compilation. In this study we used atmospheric data from four European sites combined with the FLEXPART dispersion model and a Bayesian inversion method, in order to derive emissions of nine individual hydrofluorocarbons from the whole European Geographic Domain and from twelve regions within it, then comparing our results with the annual emissions that the European countries submit every year to the United Nations Framework Convention on Climate Change, as well as with the bottom-up Emissions Database for Global Atmospheric Research. We found several discrepancies when considering the specific compounds and on the country level. However, an overall agreement is found when comparing European aggregated data, which between 2008 and 2014 are on average 84.2 ± 28.0 Tg-CO2 -eq·yr −1 against the 95.1 Tg-CO2 -eq·yr −1 reported by UNFCCC in the same period. Therefore, in agreement with other studies, the gap on the global level between bottom-up estimates of Annex I countries and total global top-down emissions should be essentially due to emissions from non-reporting countries (non-Annex I). Highlights: Bottom-up emission inventories of hydrofluorocarbons are affected by uncertainties. Atmospheric measurements combined with models are used in support to bottom-up inventories. Bottom-up and top-down estimates agree when the aggregated data are considered. When considering the specific compounds and on the country level discrepancies are found.